TOXICITY ASSESSMENT OF STEM CELLS IN SOFT TISSUE DEFECTS IN EXPERIMENTAL ANIMALS - Nishanov Zh.H., Khramova N.V.; Charyshnikova O.S.; Tsiferova N.A.; Makhmudov A.A. (Central Asian Journal of Medicine, 2025)
The article presents an experimental analysis of cytoxicity of stem cells application in deep soft tissue defects in experimental animals (rats). The dynamics of animal weight and relative weight of internal organs also did not undergo statistically significant deviations in comparison with control and reference values, which indicates the safety of the used stem cells for the organism of experimental animals.